CXCL9 expression and polyomavirus BK infectivity in renal transplant patients with nephropathy - Kariminik, A; Yaghobi, R; Dabiri, S (Cellular and Molecular Biology, 2016)
Polyomavirus BK is an important risk factor for nephropathy and renal lose after kidney transplantation. CXCL9 is a key immunoregulatory molecule which participates in stimulation and migration of immune cells to the infected sites. Thus, the main aim of this study was to evaluate the expression levels of CXCL9 mRNA and serum levels in the infected polyomavirus BK infected renal transplant patients with and without nephropathy compared with healthy controls. This cross sectional study was performed on three studied groups including: polyomavirus BK infected vs. non-infected renal transplant patients with nephropathy and healthy controls. The mRNA and serum levels of CXCL9 were evaluated on the studied patient and control samples using an in-house comparative real time PCR and ELISA methods, respectively. The mRNA expression and serum levels of CXCL9 were both increased in polyomavirus BK infected compared with non-infected renal transplant patients and also in comparing with healthy controls. This upregulation was significant in the serum level in polyomavirus BK infected vs. non-infected patients and also in comparing with controls. According to these results, polyomavirus BK can induce renal complications via stimulation of inflammatory biomarkers like chemokine. Confirmation of the increasing of the expression and production of CXCL9 as a pro-inflammatory chemokine in renal transplanted polyomavirus BK infected patients with nephropathy need to confirm in further completed studies with longer follow-up.